The Qualitative Study of Information System Utilization in Organizational Decision-Making - Joko Sarono; Abdul Jamil; Emmie Fatkhunnajah; Nurkomar Hidaya; Purwanto Purwanto (Jurnal Indonesia Sosial Sains, 2026)
Background: The use of information systems has become a crucial element in supporting organizational decision-making amidst the complexity of the business environment and demands for efficiency. Objective: This study aims to explore how information systems are utilized in organizational decision-making processes, as well as to identify the benefits, challenges, and factors contributing to their success. Methods: The study used a qualitative approach with a case study method in an organization that has implemented an integrated information system. Data were collected through in-depth interviews, observations, and analysis of internal organizational documents. Results: The results indicate that information systems play a significant role in improving decision quality by providing accurate, timely, and relevant data. However, the use of information systems has not been fully optimized due to limited user competency, resistance to change, and data integration constraints. Conclusion: This study provides a conceptual contribution to understanding the role of information systems in organizational decision-making and provides practical implications for system managers and organizational leaders in improving the effectiveness of information technology utilization.